A NEW SPECIES OF DURIO FROM BURMA - REKSODIHAEDJO, W. SOEGENG (Research Center for Biology, 1965)
In working up the sterculiaceous specimens from the Herbarium of the Indian Botanic Garden in Calcutta I have encountered a specimen of Durio which represents apparently a hitherto undescribed species. The description of this species is presented here. Gratefully I acknowledge my thanks to the Director of the Calcutta Herbarium for the loan of the specimen together with the excellent drawing from which the figure published here has been copied partly.